2016
DOI: 10.1089/ars.2015.6409
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Posttranslational Modifications of HMGB1 During Immune Responses

Abstract: Significance: High-mobility group protein 1 (HMGB1) is an evolutionarily conserved and multifunctional protein. The biological function of HMGB1 depends on its cellular locations, binding partners, and redox states. Extracellular HMGB1 is a mediator of inflammation during infection or tissue injury. Immune cells actively release HMGB1 in response to infection, which in turn orchestrates both innate and adaptive immune responses. Recent Advances: Hyperacetylation of HMGB1 within its nuclear localization sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
94
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 103 publications
(94 citation statements)
references
References 102 publications
(205 reference statements)
0
94
0
Order By: Relevance
“…The protein harbors 3 conserved cysteine residues at position 23, 45, and 106, and the redox state of these cysteines determine whether HMGB1 functions as a chemokine or as a proinflammatory cytokine (1114). HMGB1, actively secreted by activated immune cells or passively released from dying cells, is a mixture of redox isoforms with distinct posttranslational modifications (5, 15, 16). Administration of anti-HMGB1 antibodies confers significant protection in animal models of experimental sepsis, endotoxemia, ischemia reperfusion injury, trauma, hepatitis, and other syndromes (35, 17).…”
Section: Introductionmentioning
confidence: 99%
“…The protein harbors 3 conserved cysteine residues at position 23, 45, and 106, and the redox state of these cysteines determine whether HMGB1 functions as a chemokine or as a proinflammatory cytokine (1114). HMGB1, actively secreted by activated immune cells or passively released from dying cells, is a mixture of redox isoforms with distinct posttranslational modifications (5, 15, 16). Administration of anti-HMGB1 antibodies confers significant protection in animal models of experimental sepsis, endotoxemia, ischemia reperfusion injury, trauma, hepatitis, and other syndromes (35, 17).…”
Section: Introductionmentioning
confidence: 99%
“…It is becoming increasingly clear that different types of stressors and cell death modes release different redox isoforms of HMGB1 into the extracellular environment [27]. Recently, it has been shown that post-translational oxidative modifications of the three cysteine residues present in HMGB1 generate different redox isoforms that have the ability to interact with multiple diverse receptors, mediating separate inflammatory functions.…”
Section: Discussionmentioning
confidence: 99%
“…The disulfide linkage of C23 and C45 is required for the cytokine-stimulating activity of HMGB1 and C106 must remain in its reduced form as a thiol at the same time [23]. In addition, both the acetylation of HMGB1 within its nuclear localization sequences [24] and the methylation at lysine 42 [25] promote HMGB1 release by mobilizing HMGB1 from the nucleus to the cytoplasm.…”
Section: Hmgb1mentioning
confidence: 99%